1993
DOI: 10.1161/01.hyp.21.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced alcohol consumption on blood pressure in untreated hypertensive men.

Abstract: Fifty-four untreated, mildly hypertensive men whose daily alcohol consumption was £28 ml ethanol and who drank at least 4 times per week took part in a randomized, controlled crossover trial. The purpose of the trial was to test the effects of alcohol reduction on blood pressure. After a 2-week familiarization period, the participants were assigned to either a reduced alcohol drinking group or a usual drinking group for 3 weeks (experimental period 1). The situation was then reversed for the next 3 weeks (expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 30 publications
6
39
1
1
Order By: Relevance
“…The drinker subgroup showed lower BP than the non drinker subgroup in JB-women. Alcohol is a substantial risk factor for HT (64,65), but no close positive relationship was found at the individual level in this study, probably due to the small sample size. The rate of smoking was also higher in JJ than in JB, but no relationship between smoking rate and ECG ST-T change prevalence was apparent at the population level.…”
Section: Discussioncontrasting
confidence: 79%
“…The drinker subgroup showed lower BP than the non drinker subgroup in JB-women. Alcohol is a substantial risk factor for HT (64,65), but no close positive relationship was found at the individual level in this study, probably due to the small sample size. The rate of smoking was also higher in JJ than in JB, but no relationship between smoking rate and ECG ST-T change prevalence was apparent at the population level.…”
Section: Discussioncontrasting
confidence: 79%
“…69 In hypertensive subjects, the BP was 5/3 mm Hg higher in the unrestricted than during the restricted period. 70 Ueshima et al 71 also examined the effect of a 2-week period of alcohol intake and restriction using a crossover method in Japanese hypertensive patients and observed a similar BP elevation with alcohol consumption.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The above-mentioned studies 11,[14][15][16] and intervention studies [18][19][20][21][22][23] indicate that an increase in alcohol consumption is associated with a significant increase in blood pressure, whereas decreased alcohol consumption is associated with a significant decrease in blood pressure in the subjects including hypertensive participants. In this study, we found that changes in alcohol consumption linearly associated with changes in blood pressure even in normotensive subjects.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%